The Relation Dynamics Between Javanese Migrants And Lampung Community Of Lampung Selatan Regency, Lampung Province (A Study of Intercultural Communication) - Khomsahrial Romli (KOM & REALITAS SOSIAL, 2010)
This research is inquiring the relationship between Javanese immigrant and indigenous Lampungese community phenomenon in South Lampung concerning to intercultural communication. This research uses qualitative paradigm (case study) in which in-depth interview, participant observation, documentation studies are used as data compilation method. The data gathered is then analyzed descriptive qualitatively. The research concludes that Javanese immigrants use three strategies in adapting Lampungese : formal adaptation, natural adaptation, and ethnic identity manipulation. Other than expecting being accepted as Lampungese community, Javanese immigrants use manipulation strategy for economic and politic orientation. In the process of adaptation Javanese faces language, psychological and socio cultural barries. In the interaction, every individuality from each ethnic group has his own perspective and different attitude on their existence and relation toward other ethnic group. Some of Javanese and Lampungese perceiveÂ that all ethnic groups are similar and willing to have equivalent relationship, behave openly and having no distance with other ethnic group. Such type of Javanese and Lampungese are called inculusive Javanese and inclusive lampungese. On the other hand, exclusive Javanese and Lampungese are those who think that his own ethnic group is better than the other one and asking for special treatment for that reason. The research also concludes that communicationÂ and interaction dynamics between Javanese and Lampungese is going on circularly in various aspects of life, such as religion, economics, politics and social. The on going communication between the two ethnic groups can be colored by cooperation and competition. Competition is only psychological, it is not resulting conflict. Cooperation is motivated by politics, economics and relegion. For the reason of achieving the same interest, they can break the border of different ethnic group. Javanese and Lampungese ethnic groups in transmigration area in South Lampung are able to manage cultural differences so wisely that they can communicate harmoniously.